PERLINDUNGAN KONSUMEN TERHADAP MAKANAN PRODUKSI RUMAH TANGGA (KERIPIK CABE) YANG TIDAK MENCANTUMKAN LABEL KADALUARSA DI KOTA DUMAI - Maringan Tua H.D; Maria Maya Lestari; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The producer of chilli chips in the city of Dumai does not include an expired label in marketing the chilli chip product in violation of Article 8 paragraph (1) letter g of Law Number 8 of 1999 concerning Consumer Protection, the giving of the mark or label is intended so that consumers get correct information about the product. , because the decision of the correct choice of consumers regarding the goods or services needed really depends on the correctness and responsibility of the information provided by the parties concerned, so there is no legal certainty regarding the expiration of Home Industry products circulating in the city of Dumai. The purpose of writing this thesis, namely: First, to find out how the implementation of the related consumer protection law does not include expired labels in the packaging of chilli chips in Dumai and law enforcement in order to provide protection for consumers. Second, to find out how legal certainty is about the chili chips Home Industry product without including an expired label.This type of research used by the author is normative legal research. Normative legal research is literature legal research, because it makes book material the main foundation in conducting this research. This research was conducted based on normative law because this study examines the problem of legal certainty for household food products that do not have an expired label, so this study discusses more analysis regarding the implementation of the law on these products. The data collection technique in this research is literature study.From the research results, there are two main points that can be concluded. First, producers of chilli chips in the city of Dumai do not include an expired label in marketing chilli chip products that have violated Article 8 Paragraph (1) Letter g of Law Number 8 Year 1999 concerning Consumer Protection, producers do not include expiration labels because the product does not use sweeteners and food preservative, they use natural ingredients in making these chilli crackers. Second, there is no legal certainty regarding the expiration of Home Industry products circulating in the city of Dumai. Where the determination of the expiration of a product is determined subjectively, besides that the role of BPOM Dumai City has not been optimal in providing consumer protection in inclusion of expired labels on Home Industry products in the city of Dumai.Keywords: Consumer Protection - Household Production - ChipsCabe - Label Expiration